A data-limited approach for estimating fishing mortality rates and exploitation status of diverse target and non-target fish species impacted by mixed multispecies fisheries. (28th January 2019) - Walker, Nicola D; García-Carreras, Bernardo; Le Quesne, Will J F; Maxwell, David L; Jennings, Simon
Abstract: Most towed-gear bottom-trawl fisheries catch several target and myriad non-target species with the same gears at the same time. Differences in species' exposure and sensitivity to fishing mortality lead to diverse outcomes in terms of population status. We develop and apply a data-limited approach for estimating fishing mortality rates and exploitation status of all species impacted by a mixed fishery. The approach requires (i) estimates of fishing mortality F by species based on area swept by towed gears, gear efficiency, and modelled species' distributions and (ii) estimation of spawning potential ratio (SPR), by species, from cross-species relationships between maximum body size and other life history parameters. Application in the North Sea reveals per cent SPR (%SPR) (reproductive output per recruit at estimated F /reproductive output at F = 0 ) by species ranges from 2.4 to 99.3. For 10% of species, including 57% of elasmobranchs, %SPR < 20 (a limit reference point), while for 17% of species 20 < %SPR < 40, and for 72% %SPR > 40 (implying relatively high and sustainable yield and low risk of population collapse). Applications of the approach include community-wide stock status assessment, state of environment reporting, risk assessment, and evaluating effects of changes in fishing distribution and intensity.